Structural and Morphological Changes in Human Dentin after Ablative and Subablative Er:YAG Laser Irradiation - Moosavi, Horieh (J Lasers Med Sci, 2016)
Introduction: This study investigated the influence of Erbium-Doped Yttrium Aluminum Garnet (Er:YAG) laser on microhardness, chemical composition and subsurface morphology of dentin cavity walls. Methods: Forty sound human premolars were selected and randomly assigned into four groups. Class V cavities were prepared either with an Er:YAG laser (groups 1 and 2; 15 Hz, 250 mJ for enamel, 10 Hz, 200 mJ for dentin) or with a high speed handpiece (groups 3 and 4). The specimens in groups 1 and 3 served as the control, whereas those in groups 2 and 4 were exposed to subablative laser irradiation following cavity preparation (10 Hz, 50 mJ). After bisecting the specimens, one half was subjected to microhardness assessment and the other half was evaluated by SEM-EDS analysis. Results: Microhardness was significantly greater in the specimens prepared by both ablative and subablative laser irradiation (group 2) than that of the bur-prepared cavities (groups 3 and 4) (P < 0.05). The quantity of calcium ion was significantly greater in cavities prepared by the Er:YAG laser (groups 1 and 2) compared to that of the bur cavities (groups 3 and 4) (P < 0.05). Subablative irradiation improved microhardness and weight percentage of calcium ion in both laser and bur cavities, but the difference was not significant compared to that of the relevant control group (P > 0.05). Conclusion: Cavity preparation with an Er:YAG laser could be considered as an alternative to the conventional method of drilling, as it enhances the mechanical and compositional properties of lased dentin, especially when combined by subablative irradiation.